Water Resources Assessment for Karst Aquifer Conditioned River Basins: Conceptual Balance Model Results and Comparison with Experimental Environmental Tracers Evidences - Longobardi, Antonia; Cuomo, Albina; Guida, Domenico; Villani, Paolo (IntechOpen, 2011)
None